The Effect of Financial Compensation and Work Pressure on Employees’ Performance through Job Satisfaction - Muhammad Akhyar; Cepi Pahlevi; Muhammad Idrus Taba (Hasanuddin Journal of Business Strategy, 2021)
This study aims to examine and analyze the effect of financial compensation and work pressure on the performance of employees through job satisfaction in DGT Regional office of South, West and South-East Sulawesi. Data was collected by a survey method, using questionnaire instruments created by Google Form platform and distributed to all civil servants of DGT Regional office of South, West and South-East Sulawesi and are grouped into five clusters. Of the 1,701 employee population, there were 352 employees who responded. Data is then analyzed using the Structural Equation Model (SEM) with the help of the SPSS AMOS application. The results showed that financial compensation and work pressure have a significant positive effect on job satisfaction. Interestingly, both variables, financial compensation and work pressure, did not show a significant effect on employees’ performance. Job satisfaction has a significant positive effect on employees’ performance.